Coexistence of idiopathic nephrotic syndrome, celiac disease, and dermatitis herpetiformis: a rare paediatric case report - Kania-Bonicka, Zofia; Cichoń-Kawa, Karolina; Mizerska-Wasiak, Małgorzata (Pediatria Polska - Polish Journal of Paediatrics, 2026)
Idiopathic nephrotic syndrome (INS) is the most common cause of nephrotic syndrome in childhood. Celiac disease is an autoimmune gluten-dependent enteropathy, and dermatitis herpetiformis (Duhring’s disease) represents its most frequent extraintestinal manifestation. The coexistence of INS, celiac disease, and dermatitis herpetiformis constitutes an exceptionally rare clinical finding. We present the case of a 13-year-old girl diagnosed with all three conditions. Following the introduction of a gluten-free diet, complete remission of both nephrological and dermatological symptoms was achieved. This case highlights the importance of an interdisciplinary diagnostic and therapeutic approach and the need to consider gluten-related disorders in children with INS of atypical presentation.